2010
DOI: 10.1007/s12149-010-0383-9
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT stabilizes the interpretation of somatostatin receptor scintigraphy findings: a retrospective analysis of inter-rater agreement

Abstract: The present results suggest that low-dose SPECT/CT stabilizes report quality in SRS by improving inter-rater agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…SPECT/CT somatostatin receptor scintigraphy increases interobserver agreement as reported in two studies: SPECT/CT kappa (k) was reported as 0.86 in both, compared to planar imaging k of 0.56 and 0.59, respectively (148,155). Furthermore, SPECT/CT allows imaging to be compressed into a single time-point at 24 hours improving the efficiency of scheduling (155).…”
Section: Somatostatin Receptor Scintigraphy With Spect/ct For Stamentioning
confidence: 66%
See 2 more Smart Citations
“…SPECT/CT somatostatin receptor scintigraphy increases interobserver agreement as reported in two studies: SPECT/CT kappa (k) was reported as 0.86 in both, compared to planar imaging k of 0.56 and 0.59, respectively (148,155). Furthermore, SPECT/CT allows imaging to be compressed into a single time-point at 24 hours improving the efficiency of scheduling (155).…”
Section: Somatostatin Receptor Scintigraphy With Spect/ct For Stamentioning
confidence: 66%
“…111 In-DTPA-octreotide imaging of neuroendocrine tumors SPECT/CT for neuroendocrine imaging was first evaluated in mixed patient groups undergoing 123 I-MIBG, 111 In-DTPA-octreotide and 123/131 I-iodine scintigraphy (20,21,145,146). Improved diagnostic accuracy of SPECT/CT over planar and SPECT imaging has been consistently reported for SRS, frequently resulting in changes to management plans (147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157). Figure 4.…”
Section: Somatostatin Receptor Scintigraphy With Spect/ct For Stamentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of SPECT/CT on inter-rater agreement in the interpretation of SRS findings has been retrospectively studied in a series of 25 unselected patients with suspected or histologically proven NETs [38]. SRS was independently interpreted by two nuclear medicine physicians: an experienced one and an inexperienced one.…”
Section: In-111 Pentetreotide Spect/ctmentioning
confidence: 99%
“…Somatostatin receptor scintigraphy is considered to be useful for several clinical indications: the localization of primary tumor, the evaluation of disease extension (staging) and the qualification for peptide receptor radionuclide therapy (PRRT). Because receptor expression on the surface of lesion cellular membranes can be Original directly correlated with the intensity of the radiopharmaceutical uptake [1] this uptake in lesions is a significant indicator in therapy stratification with the use of somatostatin analogs labeled with 90 Y or/and 177 Lu [2][3][4][5][6][7][8]. An optimized method of single photon emission computed tomography (SPECT) image reconstruction is crucial to the interpretation of SRS images of NETs.…”
Section: Introductionmentioning
confidence: 99%